Dialektika Pada Laporan Keuangan: Analisa Kinerja Laporan Keuangan Perusahaan Sektor Farmasi yang Terdaftar Di Bursa Efek Indonesia - Ni Ketut Sriwinarti (Program Study Akuntansi, 2020)
This study aims to analyze in depth the financial statements of public companies which are a reflection of the company's holistic performance or only bits and pieces that have to be collected to become the integrity of the company's performance. The research approach used in this research is the document dialectic approach, which this approach will provide an overview of the process of finding the truth of science, especially those listed in the document text both words and numbers. The main data source in this study is the audited financial statements of the Manufacturing companies Sub-Sector Pharmaceutical in 2018 and 2019 which are listed on the IDX. Based on the analysis conducted, it was found that 40% of the company's financial statements that were presented still contained soap bubbles which meant that there was a difference in the value of the account between the 2018 report presented in 2018 and the 2018 report presented in 2019. Consistency and stability in financial presentation would be foster a sense of trust in the company, but from the data obtained, only 30% of companies are able to provide a sense of protection, 50% of companies create suspicion, 20% of companies present financial reports that cannot be enlightened so that they can have an impact that will mislead users in returning decisions the economy.